SANITASI PEMERAHAN DAN KUALITAS SUSU DI KELOMPOK TANI HARAPAN MAKMUR DI KECAMATAN KOTO TANGAH KOTA PADANG - Elly Roza; Salam N. Aritonang; Hilda Susanty; Afriani Sandra (LPPM Universitas Andalas, 2020)
Harapan Makmur Farmer Group is one of dairy farmer group in Padang. Located at Air Dingin, Balai Gadang, Koto Tangah district. Implementation of community service aims to develop a group of dairy farmers by providing knowledge in the form of the importance of hygiene and milking sanitation sanitation on milk quality. The specific target of this activity is to ensure the safety of milk consumed by the public in accordance with Indonesian National Standard (SNI) 2011 which contain minimum 3% of fat, 2.7% of protein, 8% solid non fat (SNF) and maximum contaminated with 1x106 CFU/ml of microba. This community service using the transfer knowledge method, that was counseling, discussion, and pilot project. Brochures were used to support this community service activity. Guidance and coaching for farmers were carried out periodically through coordination with the group leader. This community service program was beneficial in the implementation of science and information on hygienic maintenance of dairy cows and the application of good milking sanitation. The quality of milk produced Harapan Makmur farmer groups after this community service program has fulfilled SNI standardssuch as fat content 4.02% , protein 3.56%, and total plate count (TPC) 2.5x105 CFU/ml, but still low in SNF that is 6.95%, it’s caused by improper feeding manajement, where cows consume too much tofu dregs that contain high water content. Farmers are expected to implementa good dairy maintenance management to improve milk quality, so that it will increase the selling price which also followed by increased income and welfare of farmers.